Perancangan Interaksi Terhadap Sistem Informasi Pendukung Proses Bisnis Percetakan Menggunakan Metode Human Centered Design: Kasus CV Wins Advertising - Della Akhidatul Izzah; Ismiarta Aknuranda (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
CV Wins Advertising is a printing company that was established in 2011 in Batu City. Currently, CV Wins Advertising carries out its business processes using conventional methods such as monitoring, recording orders, and submitting orders to the production department. This has the potential to cause problems, namely loss of order records and negligence of business processes. Therefore, digitization and good interaction design are needed for the digital solutions being developed. This study aims to design interactions with information systems supporting web-based printing business processes for the monitoring process, order recording, to delivery to the production department so that order records can be stored in a structured manner and minimize negligence in business processes. The design approach used is Human Centered Design (HCD). In this study, two types of designs were produced, namely high-fidelity prototypes on computers and mobile phones. The two types of design are evaluated by users using scenario-based usability testing on the Single Ease Question (SEQ) to measure the level of difficulty. The evaluation results show that the design is easy to use and resulted in several suggestions for improvement which include detailed reports, additional content requirements for employee presence, and additional requirements in the form of notifications.